Previously Undiagnosed Spinal and Bulbar Muscular Atrophy as a Cause of Airway Obstruction after Robot-Assisted Laparoscopic Prostatectomy - Miyuki Niki; Taihei Tachikawa; Yuka Sano; Hiroki Miyawaki; Aisa Matoi; Yukari Okano; Nobutaka Kariya; Tsuneo Tatara; Munetaka Hirose (Case Reports in Anesthesiology)
Background. Preoperative vocal cord paralysis is a risk factor for postoperative respiratory distress following extubation after general anesthesia. We present an unusual case where a geriatric patient developed airway obstruction after robot-assisted laparoscopic prostatectomy. Case Presentation. A 67-year-old male, who had suffered from left vocal cord paralysis of unknown etiology, was scheduled for robot-assisted laparoscopic prostatectomy (RALP). General anesthesia was performed without any problems. The patient, however, developed airway obstruction one hour after extubation and was reintubated following commencement of mechanical ventilation for one day. At the age of 70 years, the patient received an emergency tracheostomy due to bilateral vocal cord paralysis and then was diagnosed with spinal and bulbar muscular atrophy (SBMA). Although no muscle weakness of either upper or lower extremities was observed, rocuronium showed hypersensitivity during total laryngectomy under general anesthesia. Conclusions. Vocal cord paralysis combined with postoperative laryngeal edema, the cause of which was presumed to be SBMA, likely caused airway obstruction after RALP. As neuromuscular symptoms progress gradually in patients with SBMA, muscle relaxants should be used carefully, even if patients with SBMA present no immobility of their extremities.